Evaluating the Impact of Climate Change on Sustainable Economic Development: Empirical Research in the Coastal Area of Kien Giang, Vietnam - Tran, Trang Mai; Bui, Tuan Quang; Bui, Huy Nhat (Darul Yasin Al Sys, 2024)
Alongside the economic growth in various coastal regions, including Kien Giang, the area faces non-traditional security issues, most notably marine environmental pollution due to the impacts of climate change. This study surveyed 130 households in several coastal regions of Kien Giang. It employed a multivariate regression model to assess the implications and quantify climate change's effects on economic activities. The findings indicate that most factors harm the financial activities of households living in these coastal regions of Kien Giang. This paper underscores the significance of addressing the adverse impacts of climate change on local economies. It highlights the urgent need for comprehensive strategies to mitigate these effects, ensuring the sustainable development of coastal communities in Kien Giang.